2017
DOI: 10.1111/ggi.13160
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional supplementation for activities of daily living and functional ability of older people in residential facilities: A systematic review

Abstract: Nutritional intervention with older people in residential facilities was effective in improving handgrip strength, but did not significantly improve scores for activities of daily living, balance, gait velocity or preventing death. Further studies with larger sample sizes and of high quality are required to investigate appropriate intervention methods and specific target participants. Geriatr Gerontol Int 2018; 18: 197-210.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…They found significant improvements in handgrip strength (mean difference 1.65 kg, P ¼ .04), but no difference in activities of daily living, gait velocity, or preventing death. 44 In our study, the benefits of ONS was higher in those participants with lower BMI. The subgroup with highest BMI showed little benefit from the intervention.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…They found significant improvements in handgrip strength (mean difference 1.65 kg, P ¼ .04), but no difference in activities of daily living, gait velocity, or preventing death. 44 In our study, the benefits of ONS was higher in those participants with lower BMI. The subgroup with highest BMI showed little benefit from the intervention.…”
Section: Discussionsupporting
confidence: 45%
“…Mean handgrip strength increased more in the intervention group (13.9%) than in the control group (7.2%) (P ¼ .055), 43 what is in line with our results. In addition, Tsuboi et al 44 performed a systematic review evaluating the effects of nutritional supplementation on activities of daily living and functional ability of older people in residential facilities. Eight clinical trials comprising 698 participants were included.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting analysis showed that nutritional support performed by a multidisciplinary team—as recommended in the ESPEN guideline—might fare better than simple interventions in reducing mortality risk and improving quality of life [43]. A systematic review looking at studies performed in nursing homes found an effect on handgrip strength only and not in other functional parameters [44]. A further recent review focused on various treatments for anorexia of ageing, also including pharmacologic approaches and flavour enhancement, suggests that some interventions may have an impact on energy intake and body weight, but calls for methodological improvements in the field [45].…”
Section: Management Of Malnutritionmentioning
confidence: 99%
“…These results, combined with our findings, therefore suggest that older persons with malnutrition and those at risk may not benefit from a nutritional intervention with regard to handgrip strength. On the other hand, there are also studies reporting positive effects, such as the systematic review that examined studies conducted in nursing homes [40]. We cannot exclude that handgrip strength is less sensitive to intervention changes than other measures of muscle strength.…”
Section: Discussionmentioning
confidence: 99%